Aeromonas IN CHILDREN LESS THAN 5 YEAR-OLD WITH ACUTE DIARRHEA - GUEVARA D, JOSÉ MARÍA (2002)
OBJECTIVE: To determine Aeromonas importance as diarrhea agent in children less than 5 year- old and compare its frequency with other enteropathogens. MATERIAL AND METHODS: Between 1998 and 1999 285 fecal samples were taken from children with acute diarrhea in 5 hospitals, which were then sent to Daniel A. Carrión Institute of Tropical Medicine in Cary Blairs transportation medium for processing by Aerokey II method. RESULTS: Aeromonas was the most frequent bacteria isolated among enteropathogens, mainly in children less than 2-year old and in summer, and Aeromonas caviae was the most frequent species. Aeromonas was mainly isolated in agar TCBS, employing O/129 disks to differentiate it from Vibrio cholerae. All Aeromonas were sensitive in vitro to furazolidone and neomycin. CONCLUSIONS: Aeromonas was the main etiological agent of aquous acute diarrhea in children less than 5 year-old.